2012
DOI: 10.1080/13674676.2012.698044
|View full text |Cite
|
Sign up to set email alerts
|

Work-related psychological health among clergywomen in Australia

Abstract: Drawing on the classic model of balanced affect, the Francis Burnout Inventory (FBI) conceptualises good work-related psychological health among clergy in terms of negative affect being balanced by positive affect. This paper sets out to explore the relationship between work-related psychological health and psychological type (as assessed by the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 11 publications
2
29
0
Order By: Relevance
“…More importantly, this study has tested and supported the balanced affect model of work-related psychological health by demonstrating how high levels of positive affect serve to offset high levels of negative affect in order to maintain a form of psychological equilibrium. Although a relatively new measure, the Francis Burnout Inventory has already been included in a number of studies concerning clergy workrelated psychological health, including Francis, Wulff, and Robbins (2008), Francis, Robbins, Kaldor, and Castle (2009), Robbins and Francis (2010), Brewster, Francis, andRobbins (2011), Francis, Gubb, and, Robbins, Francis, and Powell (2012), Barnard and Curry (2012), Randall (2013), and Francis, Payne, and Robbins (2013).…”
Section: Conceptualisation and Measurement Of Work-related Psychologimentioning
confidence: 99%
“…More importantly, this study has tested and supported the balanced affect model of work-related psychological health by demonstrating how high levels of positive affect serve to offset high levels of negative affect in order to maintain a form of psychological equilibrium. Although a relatively new measure, the Francis Burnout Inventory has already been included in a number of studies concerning clergy workrelated psychological health, including Francis, Wulff, and Robbins (2008), Francis, Robbins, Kaldor, and Castle (2009), Robbins and Francis (2010), Brewster, Francis, andRobbins (2011), Francis, Gubb, and, Robbins, Francis, and Powell (2012), Barnard and Curry (2012), Randall (2013), and Francis, Payne, and Robbins (2013).…”
Section: Conceptualisation and Measurement Of Work-related Psychologimentioning
confidence: 99%
“…Examples of studies using the Eysenckian model of personality are provided, for example, by Francis and Rutledge (2000), Rutledge and Francis (2004), Francis, Louden, and Rutledge (2004), Francis, Turton, and Louden (2007), Turton and Francis (2007), Francis, Robbins, Rolph, Turton, and Rolph (2010), and Wulff (2013a, 2013b). Examples of studies using psychological type theory are provided by Francis, Wulff, and Robbins (2008), Francis, Robbins, Kaldor, and Castle (2009), Robbins and Francis (2010), Robbins (2011), Francis, Gubb, and, Robbins, Francis, and Powell (2012), Francis, Payne, and Robbins (2013) and Francis and Crea (2015).…”
Section: Discontent With Both the Theoretical Model Underpinning The mentioning
confidence: 99%
“…A series of studies reported on the application of the Francis Burnout Inventory in the UK Brewster, Francis, & Robbins, 2011;Francis, Gubb, & Robbins, 2012;Randall, 2013;Francis, Payne, & Robbins, 2013). The Francis Burnout Inventory has also been used in studies conducted in the USA (Francis, Wulff, & Robbins, 2008;Barnard & Curry, 2012;Francis, Robbins, & Wulff, 2013a, 2013b, in Australia and New Zealand (Francis, Robbins, Kaldor, & Castle, 2009;Robbins, Francis, & Powell, 2012) and Italy .…”
Section: Discontent With Both the Theoretical Model Underpinning The mentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, this study has tested and supported the balanced affect model of work-related psychological health by demonstrating how high levels of positive affect serve to offset high levels of negative affect in order to maintain a form of psychological equilibrium. Although a relatively new measure, the Francis Burnout Inventory has already been included in a number of studies concerning clergy work-related psychological health, including Francis, Wulff, and Robbins (2008), Francis, Robbins, Kaldor, and Castle (2009), Robbins and Francis (2010), Brewster, Francis, andRobbins (2011), Francis, Gubb, and, Robbins, Francis, and Powell (2012), Barnard and Curry (2012), Randall (2013), and Francis, Payne, and Robbins (2013).…”
Section: Work-related Psychological Healthmentioning
confidence: 99%